Analysis Of Coconut Shell Charcoal Powder Composites With The PVAC Glue To The Impact, Bending And Sound Absorption For Acoustics Wall Application - SUHARTONO, NORMAN AGUNG, Wijianto, ST, M.Eng, Sc, Ir. Pramuko Ilmu Purboputro, MT (2014)
The aims from this study are determine the impact strength of composite and determine the bending strength of composite coconut shell charcoal and then find out the sound absorption power of coconut shell charcoal composite. In the manufacture of composite materials using coconut shell powder with an average diameter 11.89 . on 8-10 % of water level and PVAC matrix glue. The volume of fraction of composites there are 40%. 50%, 60%, and pressed the composites by using press mold method that is tightening the bolt on the mold. The test were conducted to ASTM and ANSI standards. For impact test conducted to ASTM D256-00, for bending test conducted to ASTM 790 and for sound absorption test conducted to ANSI SI13 by using five second method with one minutes for reading time. Value of impact result revealed that the highest average at 40% fraction of 0.0100 j/mm2 with 1.328 j of energy absorption and the lowest at 60% fraction of 0.0063 j/mm2 with energy absorbing o.885 j. Value of highest bending strength at 40% fraction is 0.62 MPa to 55.66 MPa modulus elasticity, whereas for bending strength the lowest result on fraction 60% that is 0.38 MPa with 22.25 MPa of modulus elasticity. For sound absorption capability of composites resulted by fraction 60% that is 3.28 dB while sound absorption capability of composites coated (sponge and plywood) resulted by fraction 60% that is 13.12 dB